2012
DOI: 10.1134/s000629791206003x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase inhibitor p21Waf1: Contemporary view on its role in senescence and oncogenesis

Abstract: p21(Waf1) was identified as a protein suppressing cyclin E/A-CDK2 activity and was originally considered as a negative regulator of the cell cycle and a tumor suppressor. It is now considered that p21(Waf1) has alternative functions, and the view of its role in cellular processes has begun to change. At present, p21(Waf1) is known to be involved in regulation of fundamental cellular programs: cell proliferation, differentiation, migration, senescence, and apoptosis. In fact, it not only exhibits antioncogenic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 114 publications
2
93
0
2
Order By: Relevance
“…GADD45A and CDKN1A (p21), both of which regulate cell cycle arrest 28,29 and are induced by p53, were significantly upregulated in v2-depleted cells compared with controls in a p53+, but not p53i, background (Figure 4d and Supplementary Figure S3B), suggesting they may contribute to the p53-dependent S-phase arrest in v2-depleted cells. On the other hand, proliferating cell nuclear antigen (PCNA), which is required for progression of DNA replication, 30 was significantly reduced in TP8i cells in both the p53+ and p53i settings ( Figure 5e).…”
Section: Resultsmentioning
confidence: 90%
“…GADD45A and CDKN1A (p21), both of which regulate cell cycle arrest 28,29 and are induced by p53, were significantly upregulated in v2-depleted cells compared with controls in a p53+, but not p53i, background (Figure 4d and Supplementary Figure S3B), suggesting they may contribute to the p53-dependent S-phase arrest in v2-depleted cells. On the other hand, proliferating cell nuclear antigen (PCNA), which is required for progression of DNA replication, 30 was significantly reduced in TP8i cells in both the p53+ and p53i settings ( Figure 5e).…”
Section: Resultsmentioning
confidence: 90%
“…p21/WAF1 is also known as cyclindependent kinase (CDK) inhibitor 1 or CDK-interacting protein 1. p21/WAF1 is a cell cycle checkpoint, where cells either set about repairing themselves or commit suicide through apoptosis (52,53). The p21/WAF1 protein functions as a regulator of cell cycle progression at the G1 phase by inhibiting cyclin-CDK2 or -CDK1 activity (52,54,55).…”
Section: +mentioning
confidence: 99%
“…Depending on its subcellular localization, p21 Cip1 displays diverse activities with respect to proliferation (Romanov et al, 2012). Using co-immunofluorescence with the germ cell marker Tra98, we found that p21…”
Section: Cip1mentioning
confidence: 99%